The prevalence of diabetes mellitus in Kazakhstan: a systematic review and meta-analysis - Kazbekova, Assem; Akanov, Zhanay; Abseitova, Dana; Buribaeva , Zhanar; Rakhymbayeva , Zhanar; Kalra, Sanjay; Baimukhanova , Manzura (Acta Biomedica Atenei Parmensis, 2024)
Background and aim: Accurately determining the prevalence of diabetes mellitus (DM) in Kazakhstan has posed challenges due to discrepancies in reported figures. This study seeks to elucidate the annual trends in diabetes mellitus prevalence in Kazakhstan based on the systematic review of the published literature.Methods: A comprehensive search was conducted in five electronic literature databases: PubMed, Web of Science, ScienceDirect, Academic Search Complete, and Google Scholar. After including initial studies, we conducted a reference search to obtain additional information.Results: Five articles met the criteria for inclusion in the systematic review. After reference search of the included articles, we added the MedInfo registry into the meta-analysis and eliminated duplicate data from the pooled prevalence estimation. Constant upward trend was observed in DM prevalence. The pooled mean DM prevalence in 2004 was 832.24 per 100,000 individuals, with significant heterogeneity observed across studies. For 2021, the pooled mean prevalence was 3743.92 per 100,000 individuals. Meta-regression revealed a significant association between DM prevalence and the male population. Sensitivity analysis identified data from 2021 as influential, contributing to publication bias.Conclusions: The study highlights an increasing trend in DM prevalence in Kazakhstan from 2004 to 2021. Gender-specific interventions may be warranted based on the association between DM prevalence and male populations. These findings underscore the need for enhanced methodologies in epidemiological studies to inform targeted public health strategies and healthcare policies addressing DM in Kazakhstan.